2011
DOI: 10.17221/3159-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors of claw lesions and lameness in pregnant sows in two types of group housing

Abstract: Claw lesions and lameness in sows are an important welfare concern as well as a cause of considerable economic loss. These problems are more common in group housing than in individual housing systems. Given that group housing for gestating sows will become mandatory in the EU from 2013 onwards, the aim of the present study was: (1) to determine the prevalence of lameness and claw lesions in sows housed in groups during gestation, and (2) to analyze whether the type of group housing system and sow-related facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
101
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(121 citation statements)
references
References 19 publications
14
101
1
1
Order By: Relevance
“…For example, infections originating in the tail can spread to other body regions via the blood stream and cerebrospinal fluid (Huey, 1996), resulting in secondary abscessation. Similarly, skin lesions can lead to the spread of secondary infection (Pluym et al, 2011) and may be the source of single-site abscessation in the limbs, flank and shoulders of pigs (Huey, 1996). In general, information on the cause of partial and whole carcass condemnation in pigs is limited (Garcia-Diaz and Coelho, 2014), and improved knowledge of the risk factors involved is needed if they are to be reduced.…”
Section: Discussionmentioning
confidence: 99%
“…For example, infections originating in the tail can spread to other body regions via the blood stream and cerebrospinal fluid (Huey, 1996), resulting in secondary abscessation. Similarly, skin lesions can lead to the spread of secondary infection (Pluym et al, 2011) and may be the source of single-site abscessation in the limbs, flank and shoulders of pigs (Huey, 1996). In general, information on the cause of partial and whole carcass condemnation in pigs is limited (Garcia-Diaz and Coelho, 2014), and improved knowledge of the risk factors involved is needed if they are to be reduced.…”
Section: Discussionmentioning
confidence: 99%
“…Lameness in sows is very common and a serious concern in pig production (Pluym et al, 2011). A lame sow is in pain, has reduced appetite, loses weight and has problems showing oestrus and conceiving (Willgert et al, 2014;Wolf, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…flooring) (Vestergaard et al, 2005). Claw lesions have been reported in young pigs (Kilbride et al, 2009b), but the prevalence appears to increase with the age of the animal and during gestation, while a temporary decrease during the lactation period has been reported (Anil et al, 2007;Pluym et al, 2011). Various sow herd survey studies have reported an incidence of claw lesions of 60-90% (KilBride et al, 2010;Olsson and Svendsen, 2002;Pluym et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations